2016
DOI: 10.7554/elife.11642
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming modulates olfactory behavior in C. elegans via endogenous RNAi pathways

Abstract: Environmental stress during early development can impact adult phenotypes via programmed changes in gene expression. C. elegans larvae respond to environmental stress by entering the stress-resistant dauer diapause pathway and resume development once conditions improve (postdauers). Here we show that the osm-9 TRPV channel gene is a target of developmental programming and is down-regulated specifically in the ADL chemosensory neurons of postdauer adults, resulting in a corresponding altered olfactory behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(89 citation statements)
references
References 98 publications
4
85
0
Order By: Relevance
“…A 25 bp sequence mediates the lag-2 promoter response to TGFβ signaling and the environment Closer inspection of the TRE upstream of lag-2 revealed homology to a cis-acting regulatory sequence named the PD motif, which was characterized in the osm-9 promoter in the context of continuous versus postdauer (PD) development (Sims et al, 2016). The osm-9 PD motif consists of two sequence elements: a DAF-3-binding site (osm-9p-DBS) and a conserved sequence (osm-9p-Cons) that is found in the upstream regulatory regions of ∼1000 genes of the C. elegans genome (Sims et al, 2016).…”
Section: Daf-7/tgfβ Signaling Promotes Lag-2 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 25 bp sequence mediates the lag-2 promoter response to TGFβ signaling and the environment Closer inspection of the TRE upstream of lag-2 revealed homology to a cis-acting regulatory sequence named the PD motif, which was characterized in the osm-9 promoter in the context of continuous versus postdauer (PD) development (Sims et al, 2016). The osm-9 PD motif consists of two sequence elements: a DAF-3-binding site (osm-9p-DBS) and a conserved sequence (osm-9p-Cons) that is found in the upstream regulatory regions of ∼1000 genes of the C. elegans genome (Sims et al, 2016).…”
Section: Daf-7/tgfβ Signaling Promotes Lag-2 Expressionmentioning
confidence: 99%
“…The osm-9 PD motif consists of two sequence elements: a DAF-3-binding site (osm-9p-DBS) and a conserved sequence (osm-9p-Cons) that is found in the upstream regulatory regions of ∼1000 genes of the C. elegans genome (Sims et al, 2016). At the lag-2 locus, we identified an 8 bp sequence with homology to the osm-9 promoter that partially overlaps with the osm-9p-DBS at −577 to −570 upstream of the lag-2 ATG (lag-2p-DBS).…”
Section: Daf-7/tgfβ Signaling Promotes Lag-2 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, stable downregulation of the guanylyl cyclase gene odr-1 in AWC neurons is required for experiencedependent olfactory adaptation to the odorant butanone, and is dependent upon MUT-7 and NRDE-3-mediated heterochromatin formation at the odr-1 locus (Juang et al 2013). Similarly, our recent work has shown that downregulation of the osm-9 TRPV channel gene in ADL neurons of animals that passed through the dauer stage is dependent upon a majority of the Mutator proteins and NRDE-3 AGO, resulting in altered responses to ascr#3 in adults (Sims et al 2016).…”
Section: Rnai Is Required In Neurons For Behavioral Adaptation To Envmentioning
confidence: 73%
“…ADL-and ASI-specific mut-16 rescue constructs were described previously (Sims et al 2016). Rab-3p::mut-16:: gfp, trx-1p::mut-16::gfp, unc-130p::mut-16::gfp, gpa-4p:: mut-16::gfp, and sre-1p::mut-16::gfp were cloned into the TOPO-XL (Life Technologies) and injected into mut-16(pk710) at a concentration of 8 ng/ml.…”
Section: Mut-16 Rescuesmentioning
confidence: 99%